Plot Scale Phosphorous and Potassium Balances of Newly Opened Wetland Rice Farming Originated from Wetland - . Sukristiyonubowo; Kusumo Nugroho; Sofyan Ritung (UNIVERSITY OF LAMPUNG, 2012)
Development of newly opened wetland rice fields both from dry land and wetland in Indonesia are important to meetrice growing demand, increase soil productivity, keep rural food security and provide jobs as well as generateincome. Most soils of newly opened rice fields are low in P and K contents, but the farmers do not apply P and Krecommended fertilisers. The study was conducted on newly opened wetland rice farming in Panca Agung village,Bulungan District, East Kalimantan Province, Indonesia in 2009. The aims were to evaluate phosphorous andpotassium input – out of newly opened wetland rice and to validate the P and K recommendation. Six treatmentswere tested including farmers practices (as control), farmer practices + straw compost + dolomite, NPK withrecommendation rate in which N and K was split in two applications, NPK with recommendation rate in which N andK was split three applications, NPK with recommendation rate + straw compost + Dolomite , in which N and K wassplit three applications, and NPK with recommendation rate + straw compost + dolomite, in which N and K weresplit two applications. The N, P and K rates were 250 kg urea, 100 kg SP-36 and 100 kg KCl ha-1 season-1, while thefarmer practices 100 kg urea and 100 kg SP-36 ha-1 season-1. Parameters to be measured were concentration P andK in mineral fertilizer, compost, irrigation water and grains as well as straw. The results showed that surplus Pranged from 5.75 to 12.85 kg P ha-1 season-1, meaning that SP-36 application rate was more than enough to replace Premoved by harvest product. In contrast, potassium application rate should be increased from 100 to 200 kg KClha-1 season-1 to fix K removed by harvest product. However, when the compost will also be increased to 3 Mg ha-1season-1 K fertilizer can be increased to 150 kg KCl ha-1 season-1 to substitute K taken away by rice harvest productand to keep higher rice grain yield. These P and K recommendation rate imply that total SP-36 and KCl should beavailable at district level will be about 984.9 Mg SP-36 and 1.477 Mg KCl district -1 season -1, respectively.Keywords: Newly opened wetland rice; nutrient balance; nutrient input; nutrient losses; plot scale wetland[How to Cite: Sukristiyonubowo, K Nugroho and S Ritung. 2012. Plot Scale Phosphorous and Potassium Balances of Newly Opened Wetland Rice Farming Originated from Wetland. J Trop Soils 17 (3): 227-237. doi: 10.5400/jts.2012.17.3.227][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.227]